The potential economic benefits of controlling trypanosomiasis using waterbuck repellent blend in sub-Saharan Africa. - Zewdu Abro; Menale Kassie; Beatrice Muriithi; Michael Okal; Daniel Masiga; Gift Wanda; Ouedraogo Gisèle; Abah Samuel; Etienne Nguertoum; Rock Aimé Nina; Philémon Mansinsa; Yahaya Adam; et al. (PLoS ONE, 2021)
Trypanosomiasis is a significant productivity-limiting livestock disease in sub-Saharan Africa, contributing to poverty and food insecurity. In this paper, we estimate the potential economic gains from adopting Waterbuck Repellent Blend (WRB). The WRB is a new technology that pushes trypanosomiasis-transmitting tsetse fly away from animals, improving animals' health and increasing meat and milk productivity. We estimate the benefits of WRB on the production of meat and milk using the economic surplus approach. We obtained data from an expert elicitation survey, secondary and experimental sources. Our findings show that the adoption of WRB in 5 to 50% of the animal population would generate an economic surplus of US$ 78-869 million per annum for African 18 countries. The estimated benefit-cost ratio (9:1) further justifies an investment in WRB. The technology's potential benefits are likely to be underestimated since our estimates did not include the indirect benefits of the technology adoption, such as the increase in the quantity and quality of animals' draught power services and human and environmental health effects. These benefits suggest that investing in WRB can contribute to nutrition security and sustainable development goals.